Psychosocial Factors Influencing Resilience in a Sample of Victims of Armed Conflict in Colombia: A Quantitative Study - Andrés Camargo; Rafael Vargas; Alexander Rincón-Rodríguez; Elena Jiménez; Martha Trujillo-Güiza (Behavioral Sciences, 2025)
Background: This study examines the psychosocial factors influencing resilience in Colombian victims of armed conflict, highlighting the role of personal, family, and community resources in mitigating trauma. Resilience is a dynamic process that enables individuals and communities to adapt to adversity. Given Colombia’s prolonged violence and forced displacement, trauma has significantly impacted both physical and emotional health. Methods: 200 adult conflict victims were recruited through snowball sampling and completed validated scales via a secure online platform. The Connor–Davidson Resilience Scale (CD-RISC-10), the APGAR Family Scale, and the Brief Resilience Coping Scale assessed resilience, social support, and psychological well-being. Results: Findings indicate that family support was strongly associated with higher resilience, with participants exhibiting higher family support scores (mean = 15.6, SD = 4.47) demonstrating significantly greater resilience (p < 0.001). Additionally, resilient coping strategies (Exp(B) = 0.772, p < 0.001) and higher subjective happiness (Exp(B) = 0.864, p = 0.001) were identified as key predictors of resilience. Significant correlations were found between resilience and mental health outcomes, with higher resilience linked to lower anxiety (ρ = −0.388, p < 0.001) and depression (ρ = −0.388, p < 0.001). Education, employment, and socioeconomic status also positively influenced resilience, with individuals with higher educational levels (χ2 = 21.265, p = 0.006) and income (χ2 = 8.945, p = 0.030) showing higher resilience scores. In contrast, alcohol consumption (Exp(B) = 0.813, p = 0.014) was negatively associated with resilience. Conclusions: This study shows that resilience in conflict victims is influenced by both individual and social factors. Strengthening family and community support, along with improving coping strategies, is essential for long-term recovery, highlighting the need for targeted interventions to enhance psychosocial well-being in affected populations.